Age and genesis of the White Pine stratiform copper mineralization, northern Michigan, USA, from paleomagnetism. Issue 2 (15th March 2013) - Symons, D. T. A.; Kawasaki, K.; Diehl, J. F.
Abstract At White Pine, the stratiform sedimentary copper (SSC) mineralization occurs mostly as chalcocite in gray‐black shales in the basal approximately 6 m of the 1081 ± 9 Ma Nonesuch Formation of the Keweenawan Supergroup. Paleomagnetic analysis of 176 specimens (19 sites) isolated collinear characteristic remanent magnetization (ChRM) directions in both magnetite and hematite in both the oxidized SSC zones and overlying pyritic and upper zones of the Nonesuch Formation. A paleomagnetic fold test shows that the normal‐polarity ChRM is prefolding in origin. Combining the ChRM directions from this study (18 sites) and from (Canadian Journal of Earth Sciences, 14, 1977, 1128; 11 sites), the Nonesuch mineralized and nonmineralized sites give a paleopole at 7.3°N, 174.7°E (N = 29, A95 = 3.0°), yielding an age of 1063 ±8 Ma on the Keweenawan apparent polar wander path. The observed 1063 ± 8 Ma age is interpreted to date both the average age of oxidation and mineralization of the SSC zone. Thus, ore genesis occurred after burial by the overlying Freda Formation and after conversion by oxidation of the underlying original clastic sediments of the Copper Harbor Formation to red beds, most likely by gravity‐driven recharge of subsurface brines by meteoric water from adjacent highlands on the southeast side of the Keweenawan Rift.